(untitled) (Al-Aasar, 2025)
Nusrat Siddiqui is a unique poet who has created a lot deep and feeling full ghazals and every kind of literature for the readers alive he wrote the stanza’s based on feeling related to the sense of human body is poetry explode the sense of saying smelling touching hearing and taste this is what the criteria he has designed to draw a brief for the readers in his poetry knows that all the sense of that can be utilised in stanza has he has observed the limits of player oriented leadership in his poetry.